Protesting the "Protest": Understanding "Non-Native" Reactions and Responses to the Six Nations Land "Occupation and Protest" in Caledonia, Ontario - Vyce, Amanda (My University, 2010)
The Six Nations land "occupation and protest" in Caledonia, Ontario, provides an important case study through which to better understand the attitudes and responses of local "non-Native" peoples to "Native" land disputes. This study explores the ways in which the residents of Caledonia think about the Six Nations claim that encompasses the land subject to the "occupation"; the ways in which the provincial and federal governments responded to the "occupation"; the tactical. activism that was employed to buttress the land claim; the response of the Ontario Provincial Police to the "occupation"; and the perception that there has been an iniquitous application of the rule of law between "Natives" and "non-Natives" leading to a system of "two tier justice" in Caledonia. This study also examines how the discourse of opposition employed by the residents of Caledonia towards the "occupation" is embedded in the liberal democratic notion of equality. I argue that vehement opposition to the Six Nations' land claim stems from the residents' desire to preserve their own economic interests, which they think would otherwise be threatened by Six Nations ownership of the disputed property. I found that the tactical activism employed by "protestors" created more tension, hostility, and concern for the residents of Caledonia than the Six Nations claim to the disputed property. Lastly, I found that many residents believe they would have been as hostile towards any group that closed down their roads and inconvenienced their daily lives, as they were with the Six Nations. Although opposition to the "occupation" was tempered by racism on the part of some individuals, I argue the concept of racism does not adequately explain the opposition arising from all individuals. Instead, opposition to the "occupation" is primarily grounded in the rhetoric of equality. The case of Caledonia is important because the "occupation and protest" has had lasting impacts on individuals from both the Six Nations and Caledonia. It has also damaged the previous harmonious and amicable relationship between the Six Nations and Caledonian communities. As well, the climate of "non-Native" public opinions towards "Native" Peoples and issues can act as a vehicle or an impediment to the settlement of "Native" land claims and the decolonization of "Native" Peoples from the state. Thus, it is important to understand the nature of local public opinions since they could impact the ability of the Six Nations to achieve swift and fair settlements to their land claims throughout the Haldimand Tract.
Keywords: Political Science; Political Science